Polygenic risk scores for mood disorders predict future strokes in women: a Mendelian randomization study. (3rd October 2022) - Goncalves, I; Borne, Y; Edsfeldt, A; Wang, Y; Pan, M; Regeneron Genetics Center,; Mellander, O; Engstrom, G; Sun, J
Abstract: Objectives: Mood disorders and strokes are often comorbid, and their health toll worldwide is huge. This study characterizes prognostic and etiological roles of mood disorders in stroke. Methods: We tested if genetic susceptibilities for mood disorders could predict future strokes using the Malmö Diet and Cancer cohort (24 631 individuals). Additionally, Mendelian randomization was employed to further examine the causality using summary statistics from large genome wide association studies (mood disorders: up to 287, 932 individuals; strokes: up to 446, 696 individuals). Results: Among 24, 366 stroke-free participants at baseline, 2, 632 individuals developed strokes, 2, 172 of them ischemic, during a follow-up of up to 25 years. After all adjustments, participants in the highest quintile (5th quintile) of polygenic risk scores (PRS) for mood disorders had 1.46x (95% confidence interval (CI): 1.22–1.74) higher risk of strokes and 1.45x (95% CI: 1.19–1.77) higher risk of ischemic strokes compared to the lowest quintile (1st quintile) of PRS in women. Univariable and multivariable Mendelian randomization analyses showed that mood disorders had causal effect on smoking (odds ratio (OR) = 1.19, 95% CI: 1.07–1.31), type 2 diabetes mellitus (T2D, OR=1.22, 95% CI: 1.04–1.43) and women's body mass index (BMI, coefficient = 0.11, 95% CI: 0.01–0.21), whereas causal effects for smoking, T2D and BMI on stroke/ischemic stroke were consistently observed. Conclusion: Our results suggest that mood disorders can cause stroke through smoking, T2D and BMI. Using PRS, women, who benefit from prevention and treatment of smoking, T2D and BMI, could possibly be early identified to prevent mood disorders and strokes. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Swedish Research Council, Swedish Heart and Lung Foundation, Skåne University Hospital Foundations, Lund University Diabetes Center - Industrial Research Center from the Swedish Foundation of Strategic Research, Region Skåne Grants, Swedish Stroke Foundation, Swedish society of medicine, Söderström König Foundation, Emil and Wera Cornell Foundation, Hjelt Foundation, and Diabetes Research and Wellness Foundation Sweden.